DISTRIBUTION OF ROOTLESS CONES AND LANDFORMS RESULTING FROM WATER-LAVA INTERACTIONS AT HAGI IN THE AÐALDALUR VALLEY (ICELAND) - Leyrit, Hervé; Ottavi Pupier, Elsa; Le Bivic, Rejanne; Bourrier, Emeline; Mathieu, Gaelle; Dujany, Arnaud; Duquennoy, Julien; Denis, Maxime (CCSD, 2024)
International audience The region of Lake Mývatn and the Aðaldalur Valley in Iceland is known for its high concentration of rootless cones. To study the processes involved in the formation of those volcanic landforms, a 1.1 km² study area rich in volcanic landforms was delineated near the Hagi guesthouse in the Aðaldalur valley. The rootless cones and other facies were referenced, and a high resolution orthomosaic and 3D model were produced using drone acquisition. A new classification of rootless volcanic cones and mounds was produced, as well as an architecture of the Hagi zone. This area is interpreted as a continuous transition of explosive interactions between lava and water followed by a basaltic flow due to depletion of water. Moreover, the lava flow mechanically erodes some of the rootless cones.